Πέρα από τη σεξουαλική χρηστικότητα: Αισθησιασμός στον σχεδιασμό προϊόντων - Χριστοδούλου, Ορέστης (My University, 2024)
This study explores the demarcation between sensuality and sexual usability in product design, identifying the key sensory elements that contribute to a sensory experience. The literature review emphasizes texture and shape as the main drivers of sensuality. The findings enhance our understanding of the characteristics of sensual design by distinguishing pornographic products that serve purely sexual purposes and attempts to identify elements that contribute to fostering a sensual connection with products that is differentiated from sexual pleasure.
Keywords: Sensuality; Sensual Design; Product Design; Sensual Design Features; Αισθησιασμός; Αισθησιακός Σχεδιασμός; Σχεδιασμός Προϊόντων; Χαρακτηριστικά Αισθησιακού Σχεδιασμού